Comparison of Minimal Excision and Primary Wound Closure with Limberg Flap Procedure in Adolescent Sacrococcygeal Pilonidal Sinus Surgery - Cem Karaali; Ali Sayan; İsmail Sert; Mehmet Üstün; Cengiz Aydin; Mustafa Emiroglu (Galenos Publishing House, 2020)
INTRODUCTION: Recently, minimally invasive methods have been used in surgical treatment of adult Sacrococcygeal pilonidal sinus (SPS) instead of classical wide excisions. However, there are fewer data about minimally invasive methods in the adolescent age group. Therefore, we aimed to compare our adolescent patients undergoing minimal excision and primary closure (MEPC) with the Limberg flap (LF) method. METHODS: In this study, the data of 80 patients who were operated for sacrococcygeal pilonidal sinus between July 2014 and December 2017 were retrospectively reviewed. Patients who underwent minimal excision with primary closure (MEPC) or Limberg flap (LF) were included in the study. Patients were evaluated in terms of age, sex, body mass index (BMI), length of hospital stay, time to return to work / school, time to complete healing, complication, recurrence and patient satisfaction levels. RESULTS: No significant difference was found between patient characteristics, complication, recurrence and patient satisfaction rates of these two groups. However, in terms of hospitalization and return to work / school, MEPC group was found to be statistically advantageous compared with LF group. DISCUSSION AND CONCLUSION: MEPC procedure has similar success in terms of recurrence, complications and patient satisfaction compared with LF. However, the MEPC procedure has advantages such as allowing faster return to work / school and not requiring hospitalization. Therefore, in adolescents with non-complex and uncommon SPS disease, MEPC procedure may be offered as an alternative treatment option to LF.